Pharmacological evidence favouring the traditional use of the root bark of Condalia buxifolia Reissek in the relief of pain and inflammation in mice. (4th December 2015) - Simões, Róli R.; Coelho, Igor S.; Junqueira, Stella C.; Maldaner, Graciela; Morel, Ademir F.; Venzke, Dalila; Ruani, Ana Paula; Pizzolatti, Moacir G.; Zanchet, Eliane M.; Santos, Adair R.S.
Abstract: Ethnopharmacological relevance: The Condalia buxifolia root bark infusion is used in traditional medicine in Brazil as antipyretic, anti-inflammatory and against dysentery. This study was designed to investigate whether the methanolic extract of the root bark of Condalia buxifolia (MECb) exhibits antinociceptive and anti-inflammatory effects in mice. Furthermore, also was investigated the involvement of glutamatergic and opioidergic system in the antinociceptive effect induced by MECb. Materials and methods: The antinociceptive and anti-inflammatory effects of intra-gastric gavage (i.g.) administered MECb (10–300 mg/kg) were evaluated in mice subjected to chemical (formalin, acetic-acid, glutamate) or thermal (hot plate) models of pain. The involvement of opioid system in the antinociceptive effect of the MECb was investigated in formalin test. Furthermore, a nonspecific effect of MECb was evaluated by measuring locomotor activity and exploratory behavior in open field test. Finally, was performed a phytochemical analysis of MECb. Results: The phytochemical analysis of MECb was performed through HPLC analysis showing that the alkaloid Condaline-A is the main constituent. The intragastric administration of MECb (100–300 mg/kg) significantly inhibited the nociception caused by acetic acid (48±2%), inflammatory phase (49±3%) and paw edema (32±6) caused by formalin, and MECb (100 mg/kg, i.g.) also inhibited nociception caused by glutamate (41±7%). In addition, MECb (100–300 mg/kg, i.g.) increased the paw withdrawal latency in hot-plate test, without affecting the locomotor activity and exploratory behavior in open field test. Finally, the antinociceptive effects of MECb (100 mg/kg, i.g.) were significantly reversed by naloxone (1 mg/kg, i.p.) in the formalin test. Conclusion: These data show, for the first time, that MECb has significant antinociceptive and anti-inflammatory effects, which appear to be related to the inhibition of the glutamatergic system and the activation of opioid mechanism, besides present central effects. These results support the use of Condalia buxifolia in traditional medicine and demonstrate that this plant has therapeutic potential for the development of phytomedicines with antinociceptive and anti-inflammatory properties. Graphical abstract: